Analisa Penerapan Total Productive Maintenance (TPM) Pada Unit Pembangkit Turbin Gas Yang Berada Di Tanjung Datuk Riau - Muhammad Razak Tuara; Anita Susilawati; Romy Romy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research aims to analyze a turbine machine of gas power plant in Tanjung Datuk, Riau by using Overall Equipment Effetiveness (OEE), which one of tool of TMP method to increase effectiveness, to improve the function and performance of machine/ equpment. To analyse of OEE values were calculated the value of availability rate, performance rate and quality rate that can used to eliminating six big losses in machine/equipment. The research methodology was collection OEE data, calculation of six big losses. Mean Time to Failure (MTTF) and Mean Time to Repair (MTTR) then statistical analyse of OEE and six big losses.MTTF and MTTR data using index of fit . From the OEE calculations obtained on the gas turbine engine was stillbelow world class (66.89%) and the target at company (90%). From the analysis of of six big losses known to affect the low value of OEE gas turbine engine that was reduce speed losses. The calculation of index of fit value of MTTF on gas turbine blade was 1,008.86 hours (42 days) and MTTR value of 1.37 hours. Therefore it would be advantage to the company in this case study to implement the pillars of TPM such as planned maintenance and autonomous maintenance to improve the effectiveness and performance of gas turbine engine for stability in supplying electricity.Keywords : Overall Equipment Effectiveness (OEE), TPM, Six Big Losses, MTTF, MTTR.